2009
DOI: 10.1073/pnas.0907988106
|View full text |Cite
|
Sign up to set email alerts
|

On the evaporation of ammonium sulfate solution

Abstract: Aqueous evaporation and condensation kinetics are poorly understood, and uncertainties in their rates affect predictions of cloud behavior and therefore climate. We measured the cooling rate of 3 M ammonium sulfate droplets undergoing free evaporation via Raman thermometry. Analysis of the measurements yields a value of 0.58 ؎ 0.05 for the evaporation coefficient, identical to that previously determined for pure water. These results imply that subsaturated aqueous ammonium sulfate, which is the most abundant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 45 publications
(56 reference statements)
7
51
4
Order By: Relevance
“…This conclusion is broadly consistent with a recent analysis of a wide range of growth kinetic measurements made on ambient aerosols at various geographic locations, which concluded that the mass accommodation coefficient must be larger than 0.1 for cloud condensation nuclei (36). It is also consistent with laboratory-based measurements that have shown that the presence of surface-active ions or low-molecular-weight organic compounds (e.g., acetic acid) have little to no effect on the evaporation coefficient (16,17). However, it must be remembered that tropospheric temperatures are largely lower than studied here.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This conclusion is broadly consistent with a recent analysis of a wide range of growth kinetic measurements made on ambient aerosols at various geographic locations, which concluded that the mass accommodation coefficient must be larger than 0.1 for cloud condensation nuclei (36). It is also consistent with laboratory-based measurements that have shown that the presence of surface-active ions or low-molecular-weight organic compounds (e.g., acetic acid) have little to no effect on the evaporation coefficient (16,17). However, it must be remembered that tropospheric temperatures are largely lower than studied here.…”
Section: Resultssupporting
confidence: 89%
“…For example, Saykally and coworkers (15) have investigated ion adsorption at water surfaces and the resulting impact on mass transfer. Although ammonium sulfate was not found to influence the evaporation kinetics of water (16), subtle effects due to the presence of more surface active perchlorate ions were observed (17).…”
mentioning
confidence: 87%
“…In our previous studies, the resulting curve was linear, 2,3,15 but in this study we observed a slight curvature and found a quadratic fit to reproduce the calibration data more accurately, especially the lower temperatures. Figure 1b shows a sample calibration curve with both linear and quadratic fits.…”
Section: 315mentioning
confidence: 42%
“…Unlike our previous measurements of ammonium sulfate solution, no icicles were observed to grow into the interaction region for sodium perchlorate solutions, meaning that interference from solid icicles both directly and indirectly (by providing a collision surface and enabling condensation back on the droplets) was not an issue. 15 This is likely due to a difference in salt crystal structure upon freezing of the solution.…”
Section: Resultsmentioning
confidence: 99%
“…Both sub-saturated (e.g. Chuang, 2003Chuang, , 2006Sjogren et al, 2007;Drisdell et al, 2009;Tong et al, 2011) and supersaturated (e.g. Winkler et al, 2004Winkler et al, , 2006Ruehl et al, 2008Ruehl et al, , 2009Lance et al, 2009;Asa-Awuku et al, 2009Shantz et al, 2010) conditions have been used.…”
Section: T Raatikainen Et Al: Activation Kinetics From Measurementsmentioning
confidence: 99%